Integration and Application of Online Sports Resources Based on Multidimensional Intelligent Technology and Resource Optimization Architecture. (3rd June 2022) - Chu, Ting
Abstract : Share the relevant factors of the overall structure of the sports network in colleges and universities, and divide the overall structure of its operation system. In view of the unequal division of educational resources, this paper proposes the construction content of the college sports network education resource sharing mechanism: the construction of college sports network education resources, the college sports network education resource sharing platform, and the management and coordination of college network education resources sharing. In the guidance of cybernetics based on the basic characteristics of network education resources, the sharing of sports network education resources is realized, so as to effectively build a scientific evaluation index system.